Awareness of developers toward sustainable affordable Housing in Malaysia - Ang, Salem; Olanrewaju, AbdulLateef; Ayob, Mohd Fairullazi (2016)
This study is concern about the delivery of sustainable affordable housing (SAH) in Malaysia. The construction, operation and demolish activities of housing has been carrying negative impacts towards environmental, social and economic. The existing review shows that lack of commitment for sustainable affordable housing among various stakeholders in housing market therefore this study aims to examine the perception, awareness and commitments of housing developers in Malaysia towards sustainable affordable housing. To achieve the aim of this research unstructured interview was used to investigate the awareness and commitments of developer toward SAH in Malaysia. The perception, awareness and commitment of developers are crucial for the sustainable development because developers have crucial roles in initiating the development with sustainable outcome. Hence, developers carry the responsibility of protecting the environment, enhance the social welfare and promote economical in sustainable affordable housing development.